Strategic Communication during Warfare: The Israeli Occupation Army's Employment of Persuasive Appeals on X Platform to Support its Psychological Operations during the Fifth War on Gaza Strip - Koa, Moeen Fathi; Nasser, Hind Abdullah (Dirasat: Human and Social Sciences, 2025)
Objectives: This study aimed to determine the extent to which the Israeli occupation army used persuasive appeals on the X platform to support its psychological operations during the Israeli aggression on Gaza in 2023/2024. Methods: The study employed a survey methodology, which belongs to descriptive research, and used content analysis to examine the tweets shared on the page, totaling 195 tweets. The content analysis form was designed based on the theoretical framework that relies on the agenda-setting theory and Aristotle's persuasion triangle, which includes three elements: Logos, Pathos, and Ethos. Results: The study results showed that Logos appeals were the most prevalent at 51.7%, followed by Pathos appeals at 31.2%, and Ethos at 17.1%. Additionally, the findings indicated that the content aligned with the page's goals and objectives, centering on particular themes. Specifically, the theme of demonstrating authority and power was the most prominent at 27.2%, while advice was the least popular topic on the page at 3.5%. Conclusions: The IDF's page on the X platform effectively uses persuasive appeals to influence the emotions and logic of the local and international public during conflicts. The page focuses on building communication messages that appeal to both emotion and reason. However, due to the lack of credibility of Israeli speakers to the public, the page does not heavily rely on them to convey its messages.